Mesenteric injury in blunt abdominal trauma in children: Is early surgical intervention need of the hour? - Amit Kumar Singh; Prateek Singh Bais; Karunesh Chand; Santosh Dey (Wolters Kluwer Medknow Publications, 2022)
Objective: There is an increasing trend of observational, nonsurgical management of abdominal injuries in children. We analyzed the feasibility and outcome of our management protocol in managing cases of the mesenteric injuries in blunt trauma abdomen in pediatric age group. Methods: Single-center retrospective analysis of pediatric trauma case records from July 2018 to March 2020 was performed. Results: Thirty-four cases of blunt abdominal trauma of whom 13 had mesenteric injuries were reviewed. The male-to-female ratio was 2.2:1, and the mean age was 9.11 ± 4.90 years. Mesentery of the small bowel was the most commonly injured segment and treatment consisted of repair of mesenteric tear, resection, and anastomosis with or without stoma formation. Conclusions: Isolated mesenteric injury of all grades should be managed either with diagnostic laparoscopy or laparotomy irrespective of hemodynamic status.